Software Engineering Approaches for Offshore and Outsourced Development 4th International Conference, SEAFOOD 2010, St. Petersburg, Russia, June 17-18, 2010. Proceedings - Nordio, Martin.; Joseph, Mathai.; Meyer, Bertrand.; Terekhov, Andrey. (Lecture Notes in Business Information Processing, 2010)
This book constitutes the proceedings of the Fourth International Conference on Software Engineering Approaches for Offshore and Outsourced Development, SEAFOOD 2010, held in St. Petersburg, Russia, June 17-18, 2010. The four long plus the four short papers presented together with two keynote speeches were carefully reviewed and selected from 25 submissions for inclusion in the book. The areas covered include industry challenges and best practices in offshore software development, distributed software development, risk management, and global software project management.